Upaya Peningkatan Kompetensi Pedagogik dan Profesional dalam Kegiatan MGMP Bahasa Inggris SMA Sumatera Barat - M. Zaim (Fakultas Bahasa dan Seni UNP, 2011)
This article aims to find out the efforts made by English Teachers’ Descussion Group (MGMP) of West Sumatra to enhance pedagogic and professional competencies as English teachers and to find out their understanding and ability to implementing those two competencies in the teaching learning process. The data were collected by questionnaires based on the indicators of the two competencies as explained in the standards of competencies published by national standards of education. The findings indicate that Most English teachers participate in MGMP activities to improve their pedagogic and professional competencies. Key Words: Teacher Competency, pedagogic, professional,